What can accelerate technological convergence of hydrogen energy: a regional perspective - Lee, Won Sang (Frontiers in Energy Research, 2023)
Focusing on technological innovation and convergence is crucial for utilizing hydrogen energy, an emerging infrastructure area. This research paper analyzes the extent of technological capabilities in a region that could accelerate the occurrence of technological convergence in the fields related to hydrogen energy through the use of triadic patents, their citation information, and their regional information. The results of the Bayesian spatial model indicate that the active exchange of diverse original technologies could facilitate technological convergence in the region. On the other hand, it is difficult to achieve regional convergence with regard to radical technology. The findings could shed light on the establishment of an R&D strategy for hydrogen technologies. This study could contribute to the dissemination and utilization of hydrogen technologies for sustainable industrial development.